The Effect of Pair Passing Exercise using the Inside Feet on Accuracy Results School Football Player Passing - Fatmala, Desi; Putra, Muarif Arhas; Putra, Deri; Manurizal, Lolia (Indonesian Journal of Sport Management, 2024)
This research was conducted because the researchers saw the low level of passing accuracy of the Singa Muda school football players (SSB). This research is a quasi-experimental research method followed by looking at the contribution of variable X to variable Y. The population in this study were 18 Singa Muda Football School (SSB) players using the Purposive Sampling technique. This research was conducted at Rambah Muda DU-SKPD football field with the method of pair passing training using the inside of the foot and taking a kick and holding the ball test. In this study, the data analysis used was the normality test analysis using the Lilliefors method, homogeneity and hypothesis testing using the t test. From the results of the analysis of the hypothesis testing of the measurements carried out on the pre-test and post-test with the same test, namely kicking and holding the ball, statistical calculations were carried out according to the formula used (t test) obtained tcount 3,249 >ttable 1,740, which means Ho is rejected and Ha is accepted. These results mean that there is an effect of pair passing exercises using the inner legs on the passing accuracy of Singa Muda Football School Players (SSB). The conclusions in this study are as follows: Paired Passing Exercises Using the Inner Legs have a Significant Effect on the Passing Accuracy of Singa Muda Football School Players (SSB) .